COCONUT INTERCROPPING WITH CASSAVA: AN ECONOMIC ANALYSIS - PRAFULLA K DAS (International Coconut Community, 1991)
An evaluation of the impact of Coconut intercropping with Cassava revealed greater returns to the resource management. Contrary to the general belief, the Cassava intercrop was even beneficial to coconut, as plots with this intercrop resulted in marginally higher yields than the plots with coconut alone.